Personal recollections of Otto Schmitt. - Geddes, L.A (IEEE Engineering in medicine and biology magazine)
The author discusses his personal recollections of Otto Schmitt, a scientist and an engineer, who contributed a lot in the advancement of biomedical engineering. The author recounts his use of Schmitt's scientific achievements such as the Schmitt trigger and the radiofrequency stimulus-isolation unit which he used in stimulating motor nerves and recording muscle action potentials with nearby electrodes. Other scientific achievements of Schmitt that the author discusses are the differential amplifier and the vectorcardiography which sprung from Schmitt's interest in electrocardiography.